2019
DOI: 10.1021/jacs.9b01033
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nanoparticle Orientations in the Self-Assembly of Patchy Quantum Dot-Gold Heterostructural Nanocrystals

Abstract: Self-assembly of nanocrystals is a promising route for creating macroscale materials that derive function from the properties of their nanoscale building blocks. While much progress has been made assembling nanocrystals into different superlattices, controlling the relative orientations of nanocrystals in those lattices remains a challenge. Here, we combine experiments with computer simulations to study the self-assembly of patchy heterostructural nanocrystals (HNCs), consisting of near-spherical quantum dots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 61 publications
10
66
1
Order By: Relevance
“…Rather, these structures are indeed an example of a systems-level design process, where the morphology at each length scale (molecular, nano, and meso) is both an effect and a cause of behavior at the others. It is important to again note that this system-derived change in NCT coordination environment is different than prior particle assembly schemes that use "patchy" particles 23,25,38 . These methods typically control particle coordination numbers by breaking the overall symmetry of the ligand shell around a particle.…”
Section: Resultsmentioning
confidence: 93%
“…Rather, these structures are indeed an example of a systems-level design process, where the morphology at each length scale (molecular, nano, and meso) is both an effect and a cause of behavior at the others. It is important to again note that this system-derived change in NCT coordination environment is different than prior particle assembly schemes that use "patchy" particles 23,25,38 . These methods typically control particle coordination numbers by breaking the overall symmetry of the ligand shell around a particle.…”
Section: Resultsmentioning
confidence: 93%
“…In the case of materials development, a designable processing approach can be executed by application of an external stimulus on the pre-defined superlattice orientation of supercrystal to develop advanced materials with a new type of mesoscale architectures. As witnessed in recent pressure-processing studies on NC supercrystals [34,61,62,63,64,65,66], it can be foreseen that this superlattice-based designable processing of materials will be certainly opening up a window for the designable fabrication of the next generation of advanced materials with an increased structural complexity and improved functionality [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The tip-patched nanoprisms could assemble into large-scale 2D lattice if the directional repulsion introduced by patches is controlled to render specific angle between the particles. Zhu et al [93] achieved the fcc superlattices from near-spherical quantum dots patched with gold satellites (Figure 4f and j), in which the orientations of individual nanoparticles are aligned. Using both small-angle X-ray scattering (SAXS, Figure 4g and k) and wide-angle electron diffraction (Figure 4h, i, l and m), they showed that by varying the ligand thickness; the degree of alignment can be controlled through the distance-dependent vdW attraction.…”
Section: Dlvo Interactionmentioning
confidence: 99%
“…From finite-element calculations, they confirmed the most favorable alignment of two nanodumbbells is the cross-stack of the particles by their patches, consistent with the unit structure of the lattice. Zhu et al [93] reported quantum dots decorated with gold patches and assembled them into close-packed structures. The molecular dynamics simulation not only reproduced their superlattices but also suggested a means of tuning the orientational alignment of the building blocks in the superlattice by varying distance-depended vdW force between the gold patches.…”
Section: Simulation Of Self-assembly Behaviors Of Patchy Nanoparticlesmentioning
confidence: 99%